2020
DOI: 10.1186/s12967-020-02322-y
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Serum sphingosine-1-phosphate levels and Sphingosine-1-Phosphate gene polymorphisms in acute respiratory distress syndrome: a multicenter prospective study

Abstract: Background: Sphingosine-1-phosphate (S1P) is a signaling phospholipid involved in pathophysiologic progression of acute respiratory distress syndrome (ARDS) through its roles in endothelial barrier function and immune modulation. We hypothesized that decreased serum S1P level is associated with the clinical outcomes of ARDS and polymorphisms in the S1P gene are associated with serum S1P levels.Methods: This multicenter prospective study includes ARDS patients and healthy blood donors as controls. Serum S1P lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…However, a study using human samples showed an opposite phenomenon. Analysis of serum S1P from 121 ARDS patients and 100 healthy individuals revealed that serum S1P levels were decreased in ARDS patients [96]; however, the BAL S1P levels in patients were not measured in this study. [93].…”
Section: Protective Role Of S1p In Experimental Acute Lung Injurymentioning
confidence: 55%
“…However, a study using human samples showed an opposite phenomenon. Analysis of serum S1P from 121 ARDS patients and 100 healthy individuals revealed that serum S1P levels were decreased in ARDS patients [96]; however, the BAL S1P levels in patients were not measured in this study. [93].…”
Section: Protective Role Of S1p In Experimental Acute Lung Injurymentioning
confidence: 55%
“…In view of this, it was suggested that S1P could be a prognostic marker to define the outcome of COVID-19. S1P serum levels were also decreased in patients suffering from acute respiratory distress syndrome (ARDS), which is a feared complication of SARS-CoV-2 (Zhao et al, 2020). The reported findings are based upon a rather small number of patients and need to be confirmed in future investigations using larger study cohorts.…”
Section: S1p As a Prognostic Marker For Sars-cov-2mentioning
confidence: 90%
“…The role of S1P and its polymorphisms in the pathogenesis of ARDS was further corroborated in a recent multicenter prospective study that determined serum levels of S1P in both ARDS patients and healthy volunteers. 62 S1P levels were dramatically decreased in ARDS. Also, lower levels of S1P correlated with greater organ dysfunction and higher Acute Physiology and Chronic Health Evaluation II scores, as well as worse ARDS-related clinical outcomes (length of stay and mortality).…”
Section: Discussionmentioning
confidence: 92%